Mechanical and thermal properties of palm-based polyurethane composites filled with Fe3O4, PANI and PANI/Fe3O4 - Liow, Chi Hao; Khairiah Hj Badri; Sahrim Hj. Ahmad (Universiti Kebangsaan Malaysia, 2011)
In-situ polymerization method was used to prepare palm-based polyurethane (PU) composites loading with 15 wt% magnetite (Fe3O4), polyaniline (PANI) and Fe3O4 coated with PANI labeled as PU15, PP and PPM, respectively. FTIR spectroscopy analysis indicated a shift in the carbonyl, C=O and NH in PP. The shift of the peak indicated that there was hydrogen bonding between the C=O (proton acceptor) of urethane with NH (proton-donator) of PANI. PPM gave the highest impact and flexural strengths at 4875 kJ/ m2 and 42 MPa, respectively but with the lowest flexural modulus (1050 MPa). Two-stage degradation behavior was observed in the TGA thermogram.